Optimization of Gracilaria sp. Seaweed Salt Purification Analysis through the Integration of Hydroextraction and Recrystallization Methods to Meet the Indonesian National Standard (SNI) for Edible Salt - hikmah, nurhikmah; Rizka Octavia; Dwi Maryana; Ahmad Jusma Azhari; Erwin (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study was motivated by the high potential of Gracilaria sp. seaweed as a source of high-quality raw material for edible salt production. However, the purification process of seaweed-derived salt often faces challenges due to the high content of non-NaCl minerals, causing the final product to fall short of the requirements specified in SNI 4435:2017 for consumption salt. Therefore, further research is needed to improve the quality and purity of the salt produced. The objectives of this study were to: (1) optimize the salt purification process from Gracilaria sp. through the integration of hydroextraction and recrystallization methods to enhance NaCl purity; (2) determine the effects of process parameter variations, including temperature, extraction time, and evaporation rate, on the quality of the resulting salt;and (3) develop technical recommendations for an efficient and environmentally friendly salt purification process. The study employed an experimental approach using a Completely Randomized Design (CRD) to evaluate variations in process temperature and duration. Salt obtained from the hydroextraction process was further purified through recrystallization to produce high-purity salt crystals. Quality analysis was conducted using gravimetric, titrimetric, and spectroscopic methods to determine NaCl content, mineral composition, and moisture content.The integration of hydroextraction and recrystallization methods effectively improved the purity of salt derived from Gracilaria sp. seaweed by increasing NaCl content and reducing impurities. The results demonstrated that the optimized purification process produced salt that met or closely approached the Indonesian National Standard (SNI) for edible salt.